Research on Expressive Writing in Psychology: A Forty-year Bibliometric Analysis and Visualization of Current Status and Research Trends - Gao, Xiaojuan (Frontiers in Psychology, 2022)
This study offers a systematic review of global academic publications of studies on expressive writing in psychology to date. By using two visualization tools VOSviewer and CiteSpace, we analyzed 1,429 articles on expressive writing from the Web of Science (WoS) Core Collection database. This study might be the first attempt at providing a visualized analysis of the existing expressive writing research. It discusses the results from the following three aspects: (1) the descriptive analysis of general results based on publications, (2) the content analysis based on highly cited articles and keyword analysis, (3) the thematic evolution based on co-word analysis and bursts detection. It is found that the application of expressive writing to minority ethnic groups might be one of the future research interests. The study proposes the necessity of conducting research in the context of positive psychology, argues for a combined use of creative and expressive writing in future studies, and suggests the potential of second/foreign language expressive writing research. The study can be used to enhance researchers’ understanding of expressive writing research and provide insights into future research opportunities in this area.